2019
DOI: 10.1007/978-3-030-18400-1_29
|View full text |Cite
|
Sign up to set email alerts
|

Agile Software Development Practices in Egypt SMEs: A Grounded Theory Investigation

Abstract: Agile information system development methods have been adopted by most software development organizations due to their proven benefits in terms of flexibility, reliability, and responsiveness. However, companies face significant challenges in adopting these approaches. Specifically, this research investigates challenges faced by software development companies in Egypt while transitioning to Agile. As little previous research is available targeting their concerns, we have conducted a grounded theory investigati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Also, companies experience gaps when implementing agile practices with missing roles, ceremonies and artefacts due to lack of staff, knowledge and finances. We also, found that, like in Egypt, novice agile practitioners find effort estimation challenging [16]. However, a surprising finding from our research was the enthusiastic adoption of communication technologies to overcome challenges of geographical distance…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Also, companies experience gaps when implementing agile practices with missing roles, ceremonies and artefacts due to lack of staff, knowledge and finances. We also, found that, like in Egypt, novice agile practitioners find effort estimation challenging [16]. However, a surprising finding from our research was the enthusiastic adoption of communication technologies to overcome challenges of geographical distance…”
Section: Discussionmentioning
confidence: 51%
“…For instance, a study conducted in Egypt revealed the positive effects on the software development process and customer satisfaction when adopting agile methodology [16]. Simultaneously, challenges were detected such as, high pressure on developers, inadequate use of effort estimation, and lack of sprint planning.…”
Section: Agile Implementation In Developing Countriesmentioning
confidence: 99%
“…Prior studies in some countries such as Ethiopia have provided empirical evidence on how the adoption of agile methods can be influenced by user involvement and the nature of the clients and contracts involved (Regassa et al, 2017). The research conducted by Mohallel and Bass (2019) discovered the positive impact of adopting agile methods on customer satisfaction and the development process in Egypt. The study, however, highlighted several problem areas for Egyptian software development companies including the use of inaccurate estimation efforts, a lack of sprint planning, and the relationship between constant pressure on the development teams and software quality.…”
Section: Agile Methods In Developing Countriesmentioning
confidence: 99%
“…Hence, early research endeavors focused on the adoption of agile methods (Nerur et al, 2005) while the tailoring of agile methods was investigated by Bass (2016b). Despite copious research on ASD in the global north, few exploratory studies exist in developing countries (Mohallel & Bass, 2019; Rahy et al, 2020; Regassa et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Although different issues connected with the implementation of agile have been raised many times by researchers from different regions (e.g. Brazil – Peitl et al ., 2018, Czech Republic – Buchalcevova, 2008, Tanzania – Rwegasira, 2017 and Egypt – Mohallel and Bass, 2019), to the best of the authors' knowledge none of these articles have focussed directly on the problem of agile understanding and expectations or dealt with empirical research conducted in several countries. Moreover, Hasan et al.…”
Section: Introductionmentioning
confidence: 99%